2007
DOI: 10.1021/jf072434k
|View full text |Cite
|
Sign up to set email alerts
|

Selenium and Aflatoxin Levels in Raw Brazil Nuts from the Amazon Basin

Abstract: Whereas selenium (Se) is an important antioxidant in human metabolism to prevent cancer, aflatoxins are highly carcinogenic. Brazil nuts from Eastern and Western Amazon regions were evaluated to find any relationship between Se and aflatoxins levels. A total of 80 (in-shell and shelled) nuts samples were collected directly from different forest sites and analyzed for Se by atomic emission spectrometry and aflatoxins by liquid chromatography tandem mass spectrometry. The limit of quantitation (LOQ) for Se was 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
2
14

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 34 publications
1
41
2
14
Order By: Relevance
“…In that study, the authors found also a correlation between levels of Se and aflatoxin: the higher the level of Se, the higher the aflatoxin contamination. Considering the fact that their correlation, as well as the levels obtained in our study is significantly lower than those reported by Pacheco and Scussel (2007), it may be possible to explain the non-detection of aflatoxins in our samples studied by the LOQ.…”
Section: Ra In Brazil Nutscontrasting
confidence: 76%
See 1 more Smart Citation
“…In that study, the authors found also a correlation between levels of Se and aflatoxin: the higher the level of Se, the higher the aflatoxin contamination. Considering the fact that their correlation, as well as the levels obtained in our study is significantly lower than those reported by Pacheco and Scussel (2007), it may be possible to explain the non-detection of aflatoxins in our samples studied by the LOQ.…”
Section: Ra In Brazil Nutscontrasting
confidence: 76%
“…The concentration of Se in Brazil nuts seems to be influenced by the absorption capacity of the tree and may vary according to factors arising from the composition of the soil from which they originate. Levels of 8.0 to 69.7 µg g -1 in shelled Brazil nuts from different regions of the Amazon have been reported by Pacheco and Scussel (2007). In that study, the authors found also a correlation between levels of Se and aflatoxin: the higher the level of Se, the higher the aflatoxin contamination.…”
Section: Ra In Brazil Nutsmentioning
confidence: 56%
“…The contents of alpha-and gamma-tocopherol in Brazil nuts are 72.55 and 74.35 mg/g of oil, respectively, and the contents of beta-sitosterol, campesterol and stigmasterol are 79.00, 4.00, and 11:33 mg/g of oil, respectively (Costa et al, 2010). Compared to other tree nuts, Brazil nuts are known as the best source of Se (Chunhieng et al, 2004;Pacheco and Scussel, 2007;Chunhieng et al, 2008;Welna et al, 2008). Furthermore, it also contains numerous vital minerals such as calcium, magnesium, phosphorus, and potassium (USDA, 2008;Yang, 2009).…”
Section: Nutritional Aspectsmentioning
confidence: 99%
“…Barium (Ba) and Radio (Ra) can also be found in Brazil nuts (Martins et al, 2012). Compared to other tree nuts, Brazil nuts are known as the best source of Se (Pacheco and Scussel, 2007;Chunhieng et al, 2008;Manfio et al, 2012). Adequate intake of Se is essential for normal activity of Se-enzymes involved in the protection against oxidative stress, maintenance of the redox system, modulating the immune system, and regulation of the thyroid.…”
Section: Compositionmentioning
confidence: 99%